Quantitative assessment and Kirschner-wire fixation of an isolated sustentaculum tali fracture in a 7-year-old girl—a case report - Mao, Fengyong; Ni, Lei; Ju, Li (Frontiers in Pediatrics, 2025)
BackgroundIsolated sustentaculum tali fractures among pediatric cohorts represent an exceedingly uncommon entity (<1% of all calcaneal fractures), with limited published evidence regarding operative intervention in prepubescent patients. Diagnostic complexities emerge from radiographically indiscernible fracture patterns, mandating cross-sectional imaging modalities. This case study documents the youngest reported patient (7-year-old female) and introduces the first comprehensive morphometric analysis of fracture characteristics and clinical outcomes following surgical management via open reduction and internal fixation (ORIF) utilizing Kirschner wire (K-wire) stabilization.Case presentationA 7-year-old female patient presented with right foot pain following a jumping trauma. Clinical assessment demonstrated point tenderness inferior to the medial malleolus with limited subtalar joint mobility. While plain radiography was non-diagnostic, computed tomography (CT) revealed a displaced sustentaculum tali fracture with a fragment measuring 13.62 × 7.89 mm and significant articular angulation (9° in the coronal plane, 16° in the sagittal plane). Surgical management consisted of ORIF utilizing two 1.5 mm K-wires to achieve anatomic reduction. The postoperative protocol included 6 weeks of cast immobilization followed by a structured rehabilitation program. At 12-month follow-up, CT imaging demonstrated complete osseous union with restoration of articular congruity. The patient exhibited optimal functional outcomes with a maximum American Orthopaedic Foot and Ankle Society (AOFAS) hindfoot score of 100, full restoration of ankle range of motion, and complete return to age-appropriate activities without sequelae.ConclusionsThis case underscores the indispensability of CT in the identification of occult sustentaculum tali fractures in pediatric patients. The quantitative parameters observed herein indicate the necessity for patient-specific evaluation protocols. K-wire fixation presents distinct advantages in the pediatric population, notably minimally invasive surgical approach and subsequent facile hardware extraction. Precise anatomical reduction remains paramount for the preservation of hindfoot biomechanics in skeletally immature patients. Although this investigation offers valuable technical insights, multi-institutional prospective studies are warranted to establish definitive surgical criteria and standardized management algorithms.